2022
DOI: 10.3390/jcm11164760
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Validation and Clinical Experience Studies in Non-Invasive Prenatal Testing for Trisomies 21, 18, and 13 and Monosomy X

Abstract: Non-invasive prenatal testing (NIPT) for trisomies 21, 18, 13 and monosomy X is widely utilized with massively parallel shotgun sequencing (MPSS), digital analysis of selected regions (DANSR), and single nucleotide polymorphism (SNP) analyses being the most widely reported methods. We searched the literature to find all NIPT clinical validation and clinical experience studies between January 2011 and January 2022. Meta-analyses were performed using bivariate random-effects and univariate regression models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 163 publications
1
18
0
Order By: Relevance
“…A recent meta-analysis evaluated the difference in rates between prospective and retrospective validation studies. 39 Both the detection and false-positive rates were significantly higher for retrospective studies (Table 2), consistent with these biases. The observed differences between prospective versus retrospective studies might also be due to an association between test performance and prevalence.…”
Section: Common Autosomal Trisomies (Cats)supporting
confidence: 63%
See 1 more Smart Citation
“…A recent meta-analysis evaluated the difference in rates between prospective and retrospective validation studies. 39 Both the detection and false-positive rates were significantly higher for retrospective studies (Table 2), consistent with these biases. The observed differences between prospective versus retrospective studies might also be due to an association between test performance and prevalence.…”
Section: Common Autosomal Trisomies (Cats)supporting
confidence: 63%
“…Numerous studies have validated the performance of NIPT for CATs and the results have been summarized in a series of meta-analyses, [35][36][37][38][39] and are summarized in Table 2. Validation studies fall into 2 main groups; (i) retrospective design in which plasma is banked and tested only after the presence or absence of aneuploidy was established (usually through CVS, amniocentesis, or phenotype at birth); (ii) prospective studies where plasma samples are tested, and fetal karyotype subsequently established through CVS or amniocentesis or based on the outcomes of the pregnancies.…”
Section: Common Autosomal Trisomies (Cats)mentioning
confidence: 99%
“…Current antenatal screening for common trisomies is based on ultrasound and cell‐free DNA analysis (cfDNA) 1–3 . Several studies have summarized the test performance of cfDNA screening and reported on a detection rate for common trisomies of about 92%–99% for a false‐positive rate of 0.1% 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several studies have summarized the test performance of cfDNA screening and reported on a detection rate for common trisomies of about 92%-99% for a false-positive rate of 0.1%. 4,5 There is an ongoing discussion on whether the scope of the cfDNA analysis should be extended to other chromosomal abnormalities, such a sex-chromosomal anomalies, rare autosomal trisomies, and structural chromosomal defects. 6 Many study groups have focused on microdeletion 22q11.2 syndrome as it belongs to the most common structural chromosomal defects.…”
mentioning
confidence: 99%
“…Currently, the availability of non-invasive prenatal screening (NIPS) has resulted in the identification of fetal aneuploidies [55], among other findings. In comparing the performance of different NIPS platforms for the common trisomies, the SNP-based method has a higher detection rate and lower false positive rate than massively parallel shotgun sequencing [56]. While NIPS is considered to have a high positive predictive value (PPV) for the detection of trisomy 21 or trisomy 18 in singleton pregnancies (99%, 97.7%, respectively) [57], the detection rate for 47,XXY is lower (93%) [58].…”
Section: Discussionmentioning
confidence: 99%